THE QUALITY OF UNTREATED INDUSTRIAL WASTERWATER AND THEIR IMPACT ON YIELD AND ITS COMPONENTS OF FIVE GENOTYPES OF WHEAT - Ahmed, Khalid KH.; Alabdraba, waleed M.; abduallah, Khalid saeed; Hindi, Husain Ali (Diyala Agricultural Sciences Journal, 2011)
Experiment was performed in the district HAWIJA - Kirkuk in winter 2007 for the purpose of studying the impact of industrial wastewater and water discharged from the North Oil Company, compared with fresh water on the yield and its components of five genotypes of wheat, soft (Ebba 99 - Sham 6 - Maxibak - Iraq - Abu Ghraib 3). The results showed that the quality of irrigation water have shown significant differences for all studied traits and the level of risk 1%, except for a recipe that the length of spike was different at the level of 5% difference did not reach the high status plant to the extent of moral statistics. As different varieties differ significantly and the level of a probability of 1% of all traits except plant height, two strands along the spike, which was not significantly different and the overlap between the items and irrigation water (species * water for irrigation) and on the moral level of a probability of 1% of the number of strands in ears and is taking place and at the level of 5 % for property ear number / plant and number of grains / ear and 1000-grain weight was not significantly different to the characteristics of plant height, ear long. Class Ebba 99 showed a clear advantage in all qualities and moral difference, followed by Sham 6 and Abu Ghraib showed a clear decline and moral qualities in all the remaining items compared to the rest of the items was a compromise between that of wastewater has shown superior in all qualities and moral difference.